SERS Nanosensors and Nanoreporters: Golden Opportunities in Biomedical Applications. (15th October 2014) - Vo‐Dinh, Tuan; Liu, Yang; Fales, Andrew M.; Ngo, Hoan; Wang, Hsin‐Neng; Register, Janna K.; Yuan, Hsiangkuo; Norton, Stephen J.; Griffin, Guy D.
Abstract : This article provides an overview of recent developments and applications of surface‐enhanced Raman scattering (SERS) nanosensors and nanoreporters in our laboratory for use in biochemical monitoring, medical diagnostics, and therapy. The design and fabrication of different types of plasmonics‐active nanostructures are discussed. The SERS nanosensors can be used in various applications including pH sensing, protein detection, and gene diagnostics. For DNA detection the 'Molecular Sentinel' nanoprobe can be used as a homogenous bioassay in solution or on a chip platform. Gold nanostars provide an excellent multi‐modality theranostic platform, combining Raman and SERS with two‐photon luminescence (TPL) imaging as well as photodynamic therapy (PDT), and photothermal therapy (PTT). Plasmonics‐enhanced and optically modulated delivery of nanostars into brain tumor in live animals was demonstrated; photothermal treatment of tumor vasculature may induce inflammasome activation, thus increasing the permeability of the blood brain‐tumor barrier. The imaging method using TPL of gold nanostars provides an unprecedented spatial selectivity for enhanced targeted nanostar delivery to cortical tumor tissue. A quintuple‐modality nanoreporter based on gold nanostars for SERS, TPL, magnetic resonance imaging (MRI), computed tomography (CT), and PTT has recently been developed. The possibility of combining spectral selectivity and high sensitivity of the SERS process with the inherent molecular specificity of bioreceptor‐based nanoprobes provides a unique multiplex and selective diagnostic modality. Several examples of optical detection using SERS in combination with other detection and treatment modalities are discussed to illustrate the usefulness and potential of SERS nanosensors and nanoreporters for medical applications. WIREs Nanomed Nanobiotechnol 2015, 7:17–33. doi: 10.1002/wnan.1283 This article is categorized under: Diagnostic Tools > Biosensing Diagnostic Tools > Diagnostic Nanodevices Diagnostic Tools > In Vivo Nanodiagnostics and Imaging